In vitro Antagonism of Trichoderma Species against Pythium aphanidermatum - Mishra*, Vinit Kumar (Journal of Phytology, 2010)
Ten strains of Trichoderma species were screened against Pythium aphanidermatum by dual culture method. Efficacy of culture filtrates of the strains was also determined. Since mycoparasitism plays important role in antagonism mechanism of Trichoderma species, extracellular enzymatic activity of the strains was assayed. Â Among the strains tested, T. viride 1433 was found most effective against P. aphanidermatum. Key words: Trichoderma species, Pythium aphanidermatum, Dual culture, Culture filtrate, Enzymatic activity <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Vinit Kumar Mishra In vitro Antagonism of Trichoderma Species against Pythium aphanidermatum. J Phytol 2/9 (2010) 28-35.